Seeing REDD. - Brown, Michael I. (Taylor & Francis, 2013)
It is now well accepted that deforestation is a key source of greenhouse gas emissions and of climate change, with forests representing major sinks for carbon. As a result, public and private initiatives for reducing emissions from deforestation and forest degradation (REDD) have been widely endorsed by policy-makers. A key issue is the feasibility of carbon trading or other incentives to encourage land-owners and Indigenous people, particularly in developing tropical countries, to conserve forests, rather than to cut them down for agricultural or other development purposes. This bo.